Memes: construção de sentidos e efeito de humor - Porto, Lilian Mara Dal Cin (2018)
This thesis has as objective to analyse how the humour is created in memes in order to make sense under the context of Textual Linguistic. It is a study subject relatively new and not widely researched, which has motived our interest. Moreover, since humour is deeply linked to culture, trying to understand what makes sense of it and hence, how effective humour is in a meme, it’s also a way to study the culture and values of a country or group, which brings more relevance to the research. We’re looking to analyse the strategies used to create sense, find the key element responsible for the humour and the meaning of it in the memes that were analysed. Among the proposed strategies, we highlighted the use of references and intertextuality, because we share the hypothesis that they are key elements in order for memes to make sense and therefore, the effective humour in memes. To accomplish our objectives e confirm our hypotheses, we based ourselves in the Textual Linguistic, in authors like Koch (2010), Custódio Filho (2011), Cavalcante (2014) and Ramos (2011; 2015). The studies about humour from Possenti, Carmelino (2009; 2015) and Travaglia (1989) were also of huge importance to this work. Shifman (2014) also contributed to meme’s definition, which was essential to this research. We’ve selected three collections of memes, that share thematic content, another there that shares compositional construction and lastly, another three that share the same style. Each one of these collections was composed by five prototypical memes, which circulated in Brazil in the year of 2015, in fifteen memes in each group in total. We concluded, based in our analyses, that memes are intertextual by nature, since they are linked to other memes that belong to the same group. However, the intertextuality seemed to go beyond this first conclusion and became the key element to understand humour. In order for a meme to make sense, it’s necessary to understand its original context or the social situation its making reference or both. Moreover, as we thought, the references in most of the memes, were a key element of the humour effect, especially in the recategorization. Also, as expected, objects of verbal and visual speech walk side by side in the process of creating sense, proving that image, indeed, can work as an object of speech and its necessary to consider it the memes reading process